2004
DOI: 10.1007/s00586-003-0588-x
|View full text |Cite
|
Sign up to set email alerts
|

Gait analysis in patients with idiopathic scoliosis

Abstract: The most significant and marked asymmetry was seen in the transverse plane, denoted as a torsional offset of the upper trunk in relation to the symmetrically rotating pelvis. This motion pattern was reflected by a ground-reaction-force asymmetry of the free rotational moment. Further studies are needed to investigate whether this behaviour is solely an expression of the structural deformity or whether it could enhance the progression of the torsional deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
93
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 8 publications
8
93
0
2
Order By: Relevance
“…GRF differences between groups are more acute for lateral stepping. Large asymmetry of GRF gait has already been demonstrated in mediolateral component [11,18]. Giakas et al [17] have shown high GRF frequencies for SG and Schizas et al [25] have shown asymmetry of vertical GRF superior to 4% in SG.…”
Section: Discussionmentioning
confidence: 96%
“…GRF differences between groups are more acute for lateral stepping. Large asymmetry of GRF gait has already been demonstrated in mediolateral component [11,18]. Giakas et al [17] have shown high GRF frequencies for SG and Schizas et al [25] have shown asymmetry of vertical GRF superior to 4% in SG.…”
Section: Discussionmentioning
confidence: 96%
“…Holden and Cavanagh [20] found that increased rearfoot pronation in during running causes significant increase in the free moment while Bleuse et al [8] found that it was related to anticipatory arm raising movements. Only, Kramers-de Quervain et al [23] reported data in adolescent idiopathic scoliosis girls. They underlined that free moment asymmetry was the single dynamic parameter related to the abnormal transverse plane acromion-pelvis alignment.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, few authors reported the use of the free moment [8,9,20,23,40]. Though the free moment measurement is useful in dynamic movement as running or walking, little attention has been paid to its measurement in standing balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific postural strategies occurring in AIS have been previously studied during upright stance [8], stepping initiation [4], walking [10] and side-stepping initiation [4]. Scoliotic patients show an increase of the amplitude of the postural oscillations [27] associated with instability [8,25] and an increased asymmetry of the dynamics of the lower limbs [5,18,29]. The variability of the parameters analysed was greater for scoliotic patients than for control subjects [4], especially in the mediolateral (ML) and anteroposterior (AP) directions [16,30].…”
Section: Introductionmentioning
confidence: 99%